Can high-speed rail increase the residents’ subjective well-being? Evidence from China - Guanglai Zhang; Ying Xiong; Guangzhao Sun; Yayun Ren; Liguo Zhang; Ning Zhang (Humanities & Social Sciences Communications)
Abstract The rapid expansion of high-speed rail (HSR) networks has significantly altered the economic behaviour of businesses and individuals, exerting a considerable impact on residents’ subjective well-being (SWB). Using the difference-in-differences (DID) methodology, this study investigates the effect of HSR inaugurations on residents’ SWB levels by utilizing panel data from the China Family Panel Studies (CFPS) spanning from 2010–2018. The results indicate that the opening of high-speed rail has elevated residents’ SWB in the areas it serves. This impact varies across city tiers and regions. Specifically, compared with non-central cities, the impact of HSR on the SWB of central city residents is more pronounced. Additionally, while the opening of HSR notably enhances residents’ SWB levels in the eastern regions, the effect is less substantial in the central and western regions. Furthermore, a comprehensive mechanism analysis underscores that HSR contributes to bolstering residents’ SWB levels by enhancing medical, educational, and natural environments in the areas it serves.